2009
DOI: 10.1160/th09-02-0118
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin clot properties are altered in patients with chronic obstructive pulmonary disease

Abstract: Increased risk of thrombotic events occurs in chronic obstructive pulmonary disease (COPD). Elevated fibrinogen and C-reactive protein (CRP), being common in COPD, are associated with formation of dense fibrin clots resistant to lysis. Statins have been found to display anti-inflammatory and antithrombotic effects. We investigated fibrin clot properties in COPD patients prior to and following statin therapy. Ex vivo plasma fibrin clot permeability, compaction, and fibrinolysis were assessed in 56 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…An electron microscopy study showed that fibrin clots isolated from the plasma of COPD patients are denser and more resistant to lysis than those from control subjects with an equivalent circulating fibrinogen concentration [11]. The same study showed that the fibrin clots from COPD patients became similar to those from subjects without COPD after 3 months of simvastatin treatment.…”
Section: Coagulopathy and Copdmentioning
confidence: 89%
See 1 more Smart Citation
“…An electron microscopy study showed that fibrin clots isolated from the plasma of COPD patients are denser and more resistant to lysis than those from control subjects with an equivalent circulating fibrinogen concentration [11]. The same study showed that the fibrin clots from COPD patients became similar to those from subjects without COPD after 3 months of simvastatin treatment.…”
Section: Coagulopathy and Copdmentioning
confidence: 89%
“…In the basal state, COPD patients exhibit abnormally high levels of tissue factor (tissue factor pro-coagulant activity) and Factor VIIa [10], and their fibrin clots are resistant to lysis [11]. After 2 h of artificial hypoxaemia, compared to non-hypoxic controls, COPD patients have abnormally elevated levels of circulating thrombin-antithrombin complex and prothrombin activation fragments, with a parallel elevation in interleukin (IL)-6 [12].…”
Section: Coagulopathy and Copdmentioning
confidence: 99%
“…The most common diseases related to thrombosis are inflammatory by nature. Reduced clot permeability and susceptibility to lysis have been observed in rheumatoid arthritis [30], chronic obstructive pulmonary disease [31], and inflammatory bowel disease [32]. Binding of C-reactive protein (CRP) with fibrinogen and fibrin [33] is likely to contribute to the prothrombotic clot phenotype as evidenced by correlations of CRP with plasma clot permeability and lysis [3032].…”
Section: Modifiers Of Fibrin Clot Propertiesmentioning
confidence: 99%
“…This could be explained by their pleiotropic effects, including anti-inflammatory and immunomodulatory effects, which was demonstrated by the significant decrease in systemic inflammation markers such as C-reactive protein and IL-6 [53, 54]. Additionally, statins were demonstrated to regulate the balance between Th1 and Th2 cells by inhibiting the Th1 development but augmenting the Th2 development of CD4 + cells [55].…”
Section: Therapeutic Implications Of Targeting Kv13-channels In the mentioning
confidence: 99%